Know your health status; not only at world health day: A community service held at the University of Namibia 2017 - Kloppers, Joan.M; Kamenye, Esther; Nauiseb-Amakali, Taimi (International Journal of Medicine, 2017)
The overall purpose of this article is to describe how the World Health Day was celebrated at the University of Namibia in 2017. University of Namibia as one of the higher institutions of learning in Namibia is celebrating the world health day yearly, mainly to promote health and prevent ill health, through partaking in the health campaigns. In 2017, the University of Namibia had conducted a mini survey and the main aims of the survey were twofold, firstly, to determine whether the students at the University of Namibia are visiting their general practitioners regularly for medical examination particular on tests like blood pressure, glucose and eye's test; and secondly to provide information about the importance of general medical check up to the students of the University of Namibia. Purposeful convenience method was used to select the sample and structural questionnaires were employed to gather data. The results revealed that the majority 34% of the students at the University of Namibia never went for medical examination to detect disease early. Recommendations were made based on the findings is that everyone to take initiative and visit any health facility (public or private) for medical examinations as soon as possible and not only to wait to be tested on world health day, since it might be too late.